Game Theory & Security Dilemma dalam Konflik Perbatasan Thailand-Kamboja - Muh. Andi Karaka Ilham (Indo Publishing, 2026)
The Thailand-Cambodia border conflict, centered on the Preah Vihear Temple, has repeatedly escalated despite numerous diplomatic efforts. This study analyzes the recurring conflict through the integrated lens of Game Theory and Security Dilemma. Using a qualitative descriptive-analytical method based on secondary data, this research argues that the persistent escalation is not merely a result of territorial disputes, but of strategic rationality trapped in a security spiral. Game Theory explains that each state’s military and diplomatic actions are calculated responses to perceived threats and expected payoffs. However, Security Dilemma reveals why these rational decisions backfire: defensive measures are misinterpreted as offensive, triggering reciprocal escalation. The findings show that Thailand and Cambodia are locked in an iterated game where mutual distrust and the lack of a credible enforcement mechanism prevent cooperation, turning rational choices into conflict-prone outcomes. This study concludes that breaking the cycle requires not only diplomatic mediation but also confidence-building mechanisms that address the perceptual roots of the dilemma.